Ethnicity can predict GLRA1 genotypes in hyperekplexia. Issue 3 (26th June 2014) - Thomas, R H; Drew, C J G; Wood, S E; Hammond, C L; Chung, S K; Rees, M I
Abstract : Objectives: Hyperekplexia is predominantly caused by mutations in the α-1 subunit of the inhibitory glycine receptor ( GLRA1 ). Three quarters of cases show autosomal-recessive inheritance. Methods: We carefully ascertained reports of ethnicity from our hyperekplexia research cohort. These were compared with all published cases of hyperekplexia with an identified genetic cause. Ethnicities were subgrouped as Caucasian, Asian, Arabic, Turkish, Jewish or Afro-American. Results: We report the ethnicity of 90 cases: 56 cases from our service augmented by 34 cases from the literature. Homozygous deletions of exons 1 to 7 are predominantly seen in people with Turkish backgrounds (n=16/17, p<0.001). In contrast, the dominant point mutation R271 is seen in people of Asian, Caucasian and African-American heritage (n=19) but not in people with Arab or Turkish ethnicities (p<0.001). Conclusions: Self-declared ethnicity can predict gene-screening outcomes. Cultural practices influence the inheritance patterns and a Caucasian founder is postulated for R271 mutations.